Dynamics of Soil Water Content Across Different Landscapes in a Typical Desert-Oasis Ecotone - Wang, Guohua; Gou, Qianqian; Hao, Yulian; Zhao, Huimin; Zhang, Xiafang (Frontiers in Environmental Science, 2020)
An understanding of soil water content dynamics is important for vegetation restoration in an arid desert oasis ecotone under different landscapes. In this study, the dynamics of soil water content under three typical landscapes (i.e. desert, sand binding shrub-land and farmland shelter woodland) were in investigated in the Hexi Corridor, northwest China, during the growing season from 2002 to 2013. The results showed that the soil water content in the deep layers decreased from 20-30% to a stable low level of 3-5% in the desert and shrub-land. But the soil water content of farmland shelter woodland decreased slightly due to irrigation. The decrease of soil water content of desert and shrub-land was mainly occurred at the deeper soil layers due to root water uptake and increased groundwater depths. The decrease of soil water content in the deep soil layers among desert-shrubland-woodland was caused by the increase of groundwater depths, as groundwater in deep depths failed to replenish the deep soil layer. This study provide new insight into the dynamics of soil water content in different landscapes in a typical desert oasis ecotone, and the results suggest that soil desiccation in the clay inter-layers due to the increase of groundwater depths could be a limited factor in water limited area.